Pelatihan Menggambar Teknik menggunakan Software Autocad di Rumah Belajar Bangkit Persada Nusantara - Arif Rakhman Suharso; Wahyu Ari Putranto; Suyono Suyono; Deri Herdawan; Yulius Oscar; Ario Hendartono (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
Technology and information have developed rapidly since entering the 20th century. In the world of industrial engineering, one of the technological developments that emerged was the use of software in drawing designs, by utilizing computerization. One of the popular software in the world of engineering is AutoCAD which displays 2D and 3D object representations. High school students need to be introduced to AutoCAD to spark their interest. This training was held at Rumah Belajar Bangkit Persada Nusantara, implemented online and attended by 10 students. The materials provided included 2D, 3D, and engineering drawings. The results of the activity showed that students were interested in studying AutoCAD. It is hoped that similar activities can be held for more advanced materials and carried out offline to be more interactive and optimal.